Appraisals para o amor: um estudo sobre a relação das mulheres com os calçados - Ortega, Caroline Teixeira (Universidade do Vale do Rio dos Sinos, 2017)
Female shoes have important role in women’s life as they represent symbols of power, elegance and sensuality. Shoes assumed love is commonly seen in our society and can be understood as a result of a set of positive emotional experiences lived by women. In this way, the shoe is perceived as belonging in a system that encompasses elements that transcend the physical aspects of the product. Under the product system scope, this study aimed to analyze experiences of ten women from 20 to 53 years old with their loved shoes from an Appraisals analysis. This analysis was made by content analysis, that enabled to conceive empiric categories which were related to seven appraisals components of Appraisals Theory. This study enable to understand the positive emotional triggers that resulted in the love by shoes. Thereby, as a result, this study relates elements which can contribute to designer to design shoes which can become loved shoes by women. Therefore, this research also contributes to women’s shoes studies and for emotional design area.
Keywords: Amor declarado por calçados; Experiências emocionais positivas; Teoria dos Appraisals; Shoes assumed love; Positive emotional experiences; Appraisals theory; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial